PERBANDINGAN KERJA ALAT PENGERINGAN TIPE SPRAY DRYER DAN FREEZE DRYER DALAM PROSES PENGERINGAN BAHAN BERBENTUK CAIR - YULISA LESTARI (LP2MTBM MAKARIOZ, 2019)
Research on the types of food drying methods has often been carried out. The research aims to obtain drying techniques that produce the best physical quality (water holding capacity, color). Drying is the separation of a small amount of water or liquid in a solid until an acceptable low value. The methods often used for drying are sunlight, oven, spray dryer, freeze dryer. Spray drying method is more preferred in the process of drying food to become powder. Spray dryer is a drying machine that is able to transform liquid into powder. The solution or liquid is sprayed into the hot air stream in the form of fine granules. This process is called the atomization process. Water quickly evaporates and the granules produce dry solid particles. The main function of the atomization process is to form a small droplet to create a large surface area for water evaporation so that drying can occur more quickly.